Durabilitas Campuran AC-WC Dengan Pemanfaatan Abu Cangkang Kemiri Dan Getah Damar Sebagai Material Substitusi: Durability of AC-WC Mixture with the Utilization of Candlenut Shell Ash and Damar Resin as Substitute Materials - Agustian, Kusmira; Yusra, Cut Liliiza; Agusmaniza, Roni (Universitas Negeri Surabaya, 2024)
Durability is one of characteristics to determine the level of asphalt mixture resistance in climate changes. This study compare resistance of AC-WC type asphalt mixtures with the use of substitute materials of candlenut shell ash and damar resin. The Firts make composition, test specimens, weighing and soakings for 30 minutes in water at temperature 60°C. The substitution levels of damar resin used are 2%,4%, and 6% of total weight of asphalt, while candlenut shell ash is 10% of the total weight of filler in the mixture. After obtaining the OAC, next make test specimens on the OAC of each type of mixture, followed by a Marshall test after being soaked for 30 minutes and 24 hours. The durability value is the result of dividing the stability value of the test specimen soaked for 24 hours by the test specimen soaked for 30 minutes. The calculation results obtained show that the use of candlenut shell ash and damar resin can increase the durability of the asphalt mixture. The highest durability was obtained at a substitution rate of 6% damar resin and 10% candlenut shell ash,117.65%, the lowest durability was obtained in a conventional asphalt mixture, which is 94.10%.